2007
DOI: 10.1126/science.1139131
|View full text |Cite
|
Sign up to set email alerts
|

Plastic and Moldable Metals by Self-Assembly of Sticky Nanoparticle Aggregates

Abstract: Deformable, spherical aggregates of metal nanoparticles connected by long-chain dithiol ligands self-assemble into nanostructured materials of macroscopic dimensions. These materials are plastic and moldable against arbitrarily shaped masters and can be thermally hardened into polycrystalline metal structures of controllable porosity. In addition, in both plastic and hardened states, the assemblies are electrically conductive and exhibit Ohmic characteristics down to approximately 20 volts per meter. The self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
261
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(272 citation statements)
references
References 14 publications
10
261
0
1
Order By: Relevance
“…In addition, some assemblies were prepared based on the interaction between stimuli‐responsive small molecular ligands 25, 80, 81. For example, metal nanoparticle supraspheres are assembled by the aggregation and cross‐link of photoactive transazobenzene dithiol (ADT) 81.…”
Section: Molecule Mediated Nanoparticle Superlatticementioning
confidence: 99%
“…In addition, some assemblies were prepared based on the interaction between stimuli‐responsive small molecular ligands 25, 80, 81. For example, metal nanoparticle supraspheres are assembled by the aggregation and cross‐link of photoactive transazobenzene dithiol (ADT) 81.…”
Section: Molecule Mediated Nanoparticle Superlatticementioning
confidence: 99%
“…This work is aimed to analyze the micromechanical response of alumina inverse opals [4,8]. Although the mechanical response of silica colloidal crystals [5], capped nanocrystals and supercrystals films [6,7,12], and polymer-stabilized or sintered aggregates [13], has been studied by nanoindentation at the nanometric length scale; similar information at the micrometric length scale of Al 2 O 3 inverse opals is not available in the open literature. In this study, nanoindentation techniques are used for reliable micromechanical characterization of Al 2 O 3 inverse opal under different contact stresses, mainly to determine the elastic and elasto-to-plastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to fabricate inverse opals by lithographic or ion beam techniques [4], self-assembly process is more flexible and cost effective for production [5,6,7]. Conventional selfassembly technologies have achieved either large area layers or highly ordered layers, but hardly both of them [8].…”
Section: Introductionmentioning
confidence: 99%
“…While previous approaches for metal aerogels were based on the modification of oxide-based aerogels with metal nanoparticles for obtaining highly catalytically active materials (Pajonk 1997;Hüsing & Schubert 1998;Campbell 2004;Jiang & Gao 2006;Vallribera & Molins 2008), with this approach the resulting highly porous macroscopic monoliths are completely non-supportedly built only from metal nanoparticles. Owing to their large surface and the lack of supporting material, these monoliths have an enormous advantage in comparison with previously reported superstructural materials from metal nanoparticles such as mesoporous platinum-carbon composites (Warren et al 2008), gold nanoparticles interlinked with dithiols (Joseph et al 2009), nanochains of hybrid palladium-lipid nanospheres as reported by Zhou et al (2009), electrocatalytically active nanoporous platinum aggregates as reported by Viswanath et al (2009), foams (Banhart 2001;Schroers et al 2003) and highly ordered two-dimensional and three-dimensional supercrystals (Kiely et al 1998;Rabani et al 2003;Fan et al 2004;Kalsin et al 2006;Shevchenko et al 2006), artificial opals (Lu et al 2005a,b), fungal templated (Bigall et al 2008a) or even non-supported assemblies of dithiol-cross-linked supraspheres (Klajn et al 2007(Klajn et al , 2008. The averaged densities of the novel metal nanoparticle hydro-and aerogels were determined to be 0.016 g cm −3 corresponding to approximately 1/1000th of the averaged bulk density of gold and silver, which is two orders of magnitude lower than that of the reported foams.…”
Section: Hydrogels and Aerogels From Noble Metal Nanoparticlesmentioning
confidence: 99%